The Castle of Well or the house of Malsen (Bulletin KNOB, 2005)
The castle of Well in the province of Gelderland probably originated in the early 14th century from a small brick residential tower situated on a castle island surrounded by a moat, possibly with a palisaded front area on the west side of the island. Apart from the fact that there is a rectangular cellar with light- or shooting chases, a water well and an entrance on the west side, there is not much to be said with any certainty about this phase.It is likely that the in the course of time the residential tower was extended on one side possibly with a walled-in courtyard with a round tower in at least one corner. Shortly before 1519 the tower was probably fitted with a clamp and heightened.Over a vaulted cellar the building acquired two floors with small windows and an attic under a hipped roof. The outer walls were probably finished with battlements on a frieze of round arcading, whereby the east wall also acquired two turrets. The design of the tower is striking in the early 16th century. A defensive character seems to have been aimed at, with very closed outer walls, turrets and battlements, in a period when all this no longer made much sense.Subsequently, probably after a French destruction in 1672, the castle was extensively refurbished. The levels were altered, whereby the new, larger windows were applied. The roof was kept in place. For a long time the castle did not change substantially, until in 1884-85 it was extended on the west side with an interconnective section and a counterpart of the residential tower.In 1928-1934 the last constructional interventions took place, among other things on the outer walls and a gate building and adjacent gate house were also added on the outer bailey.